Business consulting en gestión de calidad del servicio en EMC2 consulting S.A.C. - Toledo Ramos, Jaime Alberto (2024)
EMC2 is a company specializing in the development of metallurgical consulting services, particularly in large-scale gold mining, since 2014. However, in the past two years, the company has experienced a decline in sales. Despite this, clients have consistently rated the quality of the service highly and expressed satisfaction, recognizing the company's expertise in gold metallurgy. This expertise is a strength that could enable EMC2 to develop a portfolio of services that have not yet been explored. EMC2's services are highly valued by clients for their quality, resulting in satisfied customers. According to the information provided by EMC2 management, the main problems shown are (a) ineffective marketing strategy; (b) failure to explore new customers; (c) personnel with little knowledge of copper; (d) focus only on gold mines; (e) low profit margin in some services; (f) administration centered on only one person; (g) reduction in sales; (h) lack of equitable distribution of workload (i) cost of more detailed services; (j) service certification; (k) scarce technical staff, and it was determined that the main problem was not having developed an effective marketing strategy and the following alternative solutions were proposed to the company such as (a) positioning the brand; (b) develop a long-term marketing strategy; (c) Develop strengths-based content. The recommended solution is to implement a long-term marketing strategy over a period of six months, with an estimated investment of S/ 34,848. In a conservative scenario, this investment is projected to generate a NPV (Net Present Value) of S/ 998,339 and an IRR (Internal Rate of Return) of 644%, showing the feasibility of implementing the strategy with the company's own resources.